2000
DOI: 10.1038/sj.bmt.1702138
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-associated lymphoproliferative disease after a cord blood transplant for Diamond–Blackfan anemia

Abstract: 1-3 LPD after allogeneic bone marrow transplant (BMT) runs a more aggressive course than that after organ transplantation. Cord blood (CB) is an alternative stem cell source containing early committed progenitor cells and immature lymphocytes. 4,5 Recent reports of transplants with related and/or unrelated partially HLA-mismatched CB have shown comparable engraftment with a small dose of nucleated cells (ෂ4 × 10 7 /kg), and a lower incidence of graft-versus-host disease (GVHD) than expected with BM grafts.5-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…22 In this particular case the tumor tissue was confirmed to be of donor origin by HLA typing, and as opposed to the case reported by Ohga et al, 2 EBV DNA was identified in the cord blood using PCR. Neither of these results provides conclusive evidence of the UCB as the source of the EBV infection in this case.…”
Section: Discussionmentioning
confidence: 74%
“…22 In this particular case the tumor tissue was confirmed to be of donor origin by HLA typing, and as opposed to the case reported by Ohga et al, 2 EBV DNA was identified in the cord blood using PCR. Neither of these results provides conclusive evidence of the UCB as the source of the EBV infection in this case.…”
Section: Discussionmentioning
confidence: 74%
“…Despite the widespread prevalence of EBV infection, EBV has been directly implicated in the development of only two malignancies observed in relatively restricted geographic areas: Burkitt's Lymphoma in East Africa and nasopharyngeal carcinoma in Southern China. It has also been closely associated to Hodgkin's Disease, thymic lymphoepithelioma, opportunistic B-cell lymphomas, pleural B-cell lymphomas or pyothorax associated B-cell lymphomas, opportunistic T-cell and NK-cell lymphomas in immunodeficiencies, primary nasal T-cell and NK-cell lymphomas, gastric carcinoma, and most recently, invasive breast carcinoma (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Epstein-barr Virus (Ebv) Is a Common Humanmentioning
confidence: 99%
“…[3][4][5][6][7] More recently, Brunstein et al at the University of Minnesota investigated the incidence of EBV-related complications in 335 patients undergoing CBT and documented an overall rate of 4.5% (total 15 cases, with 5 adults) with an incidence of 3.3% in recipients of myeloablative transplantations, 7% for nonmyeloablative transplantations and up to 21% among the subset of patients who received also ATG, suggesting a significantly higher risk of EBV-related complications in recipients of a nonmyeloablative preparative regimen with ATG. 8 The lower incidence of EBV-viremia and PTLD reported in earlier series may, at least in part, be related to the recent introduction of effective and highly sensitive techniques for quantitative measurements of EBV load and sequential monitoring of EBV reactivation.…”
mentioning
confidence: 99%
“…Fifty-six of these patients had participated in registrational trials and the results of tumor response and toxicity (but not related to ALC) are included in previous publications. 4 Rituximab-refractory patients were classified as patients who did not respond or relapsed within 6 months of rituximab therapy before ibritumomab tiuxetan therapy. All patients were treated with 90 Y ibritumomab tiuxetan 0.4 mCi/kg (maximum of 32 mCi) as described previously.…”
mentioning
confidence: 99%
See 1 more Smart Citation